Using Indigenous Knowledge to Raise Agricultural Productivity : An Example from India - Prakash, Siddhartha (World Bank, Washington, DC, 2012)
The note examines the transfer of knowledge from one generation to the next, and from country to country, through trading ties, and social interactions which has raised knowledge sharing activities within Africa, and elsewhere. Such activities have reinforced the universality of indigenous knowledge, and, despite geographical differences, the note looks at the Sodic Lands Reclamation Project in India, as a good example of integration of traditional knowledge into Bank-supported operations. The first challenge the project presented was the treatment of high build-up of salts in the fields, with high concentrations of exchangeable sodium in which finer soil particles are dispersed, but where water and air cannot penetrate. These sodic soils are toxic to plants, and adversely affect agriculture, human, and plant health. The application of traditional knowledge, i.e., spreading gypsum, building bunds, leaching the soil, starting multi-cropping, green manuring and crop rotation, as well as using compost and plowing the land, maintained a continuous ground cover, through intensive cropping, which protected the soils from a return of surface salts. The result was a substantive reduction in the damage caused by brown plant hoppers from 49 percent down to 2 percent. This was conducive to innovative strategies, drawing upon indigenous resources, and knowledge about agricultural practices, practices institutionalized by the formation of a Farmers Field School, community participation in irrigation, and training provided to women through the farmers school in agricultural practices.